2019
DOI: 10.1111/jog.13916
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐trimester glycosylated hemoglobin levels (HbA1c) and its correlation with oral glucose tolerance test (World Health Organization 1999)

Abstract: Aim The aim of the present study was to assess the role of hemoglobin A1c (HbA1c) in screening of gestational diabetes mellitus (GDM) and to compare its efficacy with 75 g oral glucose tolerance test (OGTT) (World Health Organization [WHO]) screening criteria. Methods A prospective observational study was performed on a total of 260 women attending antenatal outpatient department of our hospital at 24–28 weeks of gestation. All women underwent 75‐g OGTT testing, and WHO 1999 criteria was used for diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In the current study, the median HbA1c level was significantly higher in women with GDM compared with women who had no GDM (4.8% vs 4.6%, P = .001). These findings are in agreement with the previous studies which reported a significantly higher HbA1c values in women with GDM compared with HbA1c values in women without GDM 10‐14 …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, the median HbA1c level was significantly higher in women with GDM compared with women who had no GDM (4.8% vs 4.6%, P = .001). These findings are in agreement with the previous studies which reported a significantly higher HbA1c values in women with GDM compared with HbA1c values in women without GDM 10‐14 …”
Section: Discussionsupporting
confidence: 93%
“…This finding was similar to the previous studies findings 10,16‐19 which reported that HbA1c values cannot replace OGTT for the diagnosis of GDM. On the other hand, several previous studies have shown a high efficiency with a good/excellent reliability of HbA1c for the diagnosis of GDM in which the AUC values ranged from 0.805 to 0.937 12,14,21 . Interestingly, in a recent meta‐analysis enrolling 6406 pregnant women in eight studies, a good level of diagnostic accuracy (AUC = 0.825) of HbA1c for the diagnosis of GDM has been reported 20 …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations